Artificial Neural Network Method in Predicting the Amount of Manila Duck Meat Production by Province in Indonesia - Joko Pamungkas; Riki Winanjaya; Wendi Robiansyah (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
Duck meat is a source of animal protein that many Indonesians need because it can increase nutritional needs to improve people's quality of life. One of the types of ducks used in this study is the Manila duck, this type of duck was chosen because it is very easy to maintain and the price is also relatively affordable. Based on data on the production of Manila ducks in Indonesia from several provinces, the annual production amount is unstable. Therefore, it is important to make predictions about this matter as information for the government. The data sample used in this study is manila duck production data taken from the Indonesian Central Statistics Agency in 2017-2020. This research uses backpropagation algorithm. Based on the results of the analysis, the best architectural model is 3-6-1 which will later be used to predict the amount of manila duck meat production in 2022 because it has the highest accuracy rate compared to other models, which is 74%. MSE Testing is 0,00412. Based on this model, predictions of the amount of manila duck meat production will be made based on provinces in Indonesia. From the prediction results, it can be seen that there are 25 provinces that are estimated to experience an increase in production in 2022 or around 73,5% (25 provinces) of a total of 34 provinces in Indonesia. Meanwhile, 9 other provinces experienced a decline or around 26,5%.